(3McGe GdYGde GdLOO (B/s - (3HjdLQ,Lhfs; (3GSeGYjd,OGhOs ((3eUQ(B: s (3OGQ eUQ GdeMQhSI(B, s, 2003)
(3Cf GdeTGgO GdKdGKI GdJj SLdgG gPG GdcJGH dG JTcd Shi GdaUd GdGhd ef gPg GdJQGLjOjG GdYdKjI GdJj dG jOQj GMO cja SJJYGbH aUhdgG , gd SjJecf McGe GdYGde GdLOO ef aQV GdgjefI Ydi GdYGde h GdefWbI GdYQHjI aj ebOeJg h Ydi QCSg? gd SjfJgj GdCeQ HGfJUGQ GdbWH GdChMO h aQV gjefJg GdefaQOI Ydi Gdchf HCSQg ?gd SJchf gPg gj fgGjI GdJGQjNh GfJUGQ GdMVGQI GdZQHjI aj UQGYgG dJcJSM CeGegG cd eG CbGeJg TYhH GdYGde ef MVGQGJ Ydi EeJOGO JGQjNgG? h gd Sjchf gPG gh NJGe GdeSQMjI h fgGjJgG dJhGLg gPg GdbhI GdWGZjI GdHGZjI, h Jchf dMXI JMdjb Pdc GdWGFQ GdLGQM GdeaJQS aj GdPQhI GdYdjG ef GdaVGA gj PGJgG GddMXI GdJj JDPf HSbhW h GfSOGd GdSJGQ Ydjg h eh jYGfj GdgRjeI GdeQjQI GdJj jdbGgG YGOI LejY GdWZGI(B.s
Keywords: (3Gdedhc h GdMcGes